Rationalize the denominator and simplify: 6 + 2 2 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hey you elton wtf!!!
In the third step you wrongly typed it as 3 − 1 . actually it should be 3 − 1 = 2 or 3 2 − 1 2 = 3 − 1 = 2
Problem Loading...
Note Loading...
Set Loading...
6 + 2 2 2 = 2 ( 3 + 1 ) 2 2
= ( 3 + 1 ) 2 × 3 − 1 3 − 1
= 3 − 1 2 ( 3 − 1 )
= 3 − 1